EVALUASI PROGRAM AKSELERASI DI SMP NEGERI KOTA AMBON - Tuhurima, David (Universitas Kristen Satya Wacana, 2016)
This research is aimed to evaluate acceleration program in SMP Negeri 6 Ambon which isÂ include four components such as: (1)Context (2)Input (3) Process, and (4)Product. This is anÂ evaluative research using descriptive analysis. This research informants are principals, viceprincipals, program coordinators, teachers, school committees, parents, and students accelerated program. Research sites in SMP Negeri 6 Ambon. The data is collected using interview, observation and documentation study techniques. For the data validation, this research used triangulation of sources and techniques. The results shows that, from context, the implementation of the acceleration program is a schoolâs initiative as an effort to address the needs and provide the education services for special smart learners (IQ ï³ 130) as well as the effectiveness of school facilities and infrastructure utilization. From the point of input including: (a) the program policy, the school has permission from the department as the juridical basis forÂ accelerated program implementation, and (b) planning program: recruitment of learners are in accordance with the criteria, curriculum acceleration program already differentiated, educatorsÂ (teachers) already meets the qualifications and criteria as teacher in class acceleration, infrastructure and financing program is sufficient to support the accelerated program. In terms of Process, acceleration program in SMP Negeri 6 Ambon has been implemented in accordance with the planning program, although there are still some shortcomings and obstacles. Recruitment of learners already implemented, curriculum adjustments will only be visible on the implementation of the teaching and learning activities, educators (teachers) are still there who do not meet the qualifications and criteria as a teacher in class acceleration, infrastructure is not sufficient to support an accelerated program of activities, and financing programs that is still lacking. The implementation of the teaching and learning process in an accelerated program carried out on a daily basis according to the effective education calendar prepared by the school. The obstacles in the implementation of the accelerated program associated with governmentÂ policy on the closure of the accelerated program. Product of the implementation of an accelerated program at SMP Negeri 6 Ambon that learners can complete their education exactly two years, passed 100%, and is accepted in favorite high school, both public and private. Thus, the implementation of accelerated program at SMP Negeri 6 Ambon should be continued but with improvements. For the further service, the school is suggested to improve the service toward accelerated program learners with providing the needs related to the implementation of the program, and for the education department, related to the monitoring, supervision, and evaluation toward the implementation of accelerated program, especially in SMP Negeri 6 Ambon.